Meningkatkan Hasil Belajar Passing Bawah Bola Voli Melalui Media Dinding Di Kelas IX Siswa SMP Negeri 2 Muara Bungo - Lisye Perina (Jurnal Muara Olahraga, 2023)
Abstract The problem in this study is the mastery of the underhand passing technique which is not optimal. This is because when performing the underhand passing technique the two arms are not tight and straight as required to perform the correct underpassing technique. This study aims to try out the volleyball passing modification method which is expected to improve student learning outcomes. Learning volleyball passing is expected to increase the maximum completeness criteria (KKM). This research is a Classroom Action Research (CAR). This research was conducted in two cycles, each cycle consisting of planning, implementation, action, observation, and reflection. The subjects of this research were 20 students of Class IX at SMP Negeri 2 Muara Bungo. Data on the results of learning to pass volleyball in class IX students were obtained through performance tests, observation sheets used to collect data on student activities in participating in the learning process of passing volleyball with the media wall. The results of the study showed that the results of learning to pass volleyball using wall media for Class IX students at SMP Negeri 2 Muara Bungo can improve learning outcomes so that they can achieve KKM scores. The increase in student learning outcomes for Class IX students at SMP Negeri 2 Muara Bungo can be seen from the significant increase from cycle I to cycle II. This can be seen from the increase in learning outcomes from cycle I to cycle II. In cycle I 60% in the complete category the number of students who completed was 12 students. In cycle II there was an increase in students in the complete category of 90% with the number of students who completed being 18 students. Keywords: Passing, Volleyball, wall media, Grade IX students